Dinuclear platinum(II) sulfide-thiolate complexes [Pt2(μ-S) (μ-SR)(PPh3)4]+ containing fluorinated substituents and the identification of a S⋯C6F5 π interaction in the crystal structure of [Pt2(μ-S)(μ- SCH2C6F5)(PPh3)4]BPh 4·2C - Henderson, W. (2014)
10.1016/j.ica.2010.12.020